Optimization study properties of Corn Cob/Polyvinyl Alcohol/Glycerol Biodegradable film considering the effect of chemical composition - Yong, Kai-Jun (2022)

(untitled)
In this study, the blended film was made from mixture of corncob powder (CCP)/polyvinyl alcohol (PVA)/glycerol by solution casting method. Various mixtures were prepared by adjusting the loading of CCP and composition of glycerol based on the result from statistical optimization tool. The functional group of CCP and every PVA/CCP/glycerol blended film were determined by Attenuated Total Reflectance Spectroscopy (ATR). Besides, the mechanical properties of every PVA/CCP/glycerol blended film were analyzed by using tensile test in order to determine its tensile strength, elongation at break and elastic modulus. Based on the result, the highest tensile strength and elastic modulus obtained were 11.46MPa and 209.9MPa respectively while the minimum elongation at break obtained was 11.78%. The mechanical properties of each of the blended film were then further studied by using statistical optimization tool where Analysis of Variance (ANOVA) and Three Dimension (3D) Surface Plot take place.